Avaliação do comportamento ao fogo de placas de vedação de concreto com inserção de resíduos de pneus inservíveis - Simonetti, Camila (Universidade do Vale do Rio dos Sinos, 2020)
The inappropriate disposal of waste tires represents a major concern regarding the mitigation of sanitary and environmental impacts from this action. This issue has motivated several studies on possible methods for reusing these elements. Civil construction can be a potential consumer of this type of waste due to the following reasons: its capacity for consuming large amounts of materials, its search for alternatives to overcome the shortage of raw materials, its interest in reducing the environmental footprint from construction projects, and its capacity to encapsulate contaminants in the cement matrix. The possibility of incorporating waste tires residue into concrete has already been consolidated in several previous studies, but there is a gap in the knowledge about how the concrete made with recycled tire materials behaves when exposed to high temperatures. This study aims to investigate the performance of precast concrete panels made with waste tires residues when exposed to fire when using the recycled steel fiber and the recycled rubber aggregate separately. The experimental design consisted in essays for the characterization of the physical and mechanical properties of the concrete produced with the recycled materials, as well as fire reactions and fire resistance tests. Besides the reference concrete without any residues, mixtures were prepared containing rubber particles used as partial replacement of fine aggregate at a proportion of 5% and 10% in volume, and other mixtures containing recycled steel fibers included at 0.5% and 1.5% of total volume. In terms of fire reaction, the results indicated that both groups of concretes with residues, unlike the conventional concrete, were classified as combustible due to the presence of sustained flaming during non-combustibility tests. There was neither flame propagation nor the register of smoke optical density. In the fire resistance tests, the recycled steel fiber reinforced concretes and those containing 5% recycled rubber aggregate presented similar behavior when compared to the conventional concrete on thermal insulation, sealing, and stability. The concrete made with 10% recycled rubber aggregate registered the occurrence of explosive spalling and worse thermal insulation and sealing.
Keywords: Segurança contra incêndio; Reação ao fogo; Resistência ao fogo; Placa de vedação de concreto; Pneu inservível; Fire safety; Fire reaction; Fire resistance; Precast concrete panels; Waste tire; ACCNPQ::Engenharias::Engenharia Civil